2007
DOI: 10.1254/jphs.fp0060911
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Na+/Ca2+ Exchanger in Ouabain-Induced Inotropy and Arrhythmogenesis in Guinea-Pig Myocardium as Revealed by SEA0400

Abstract: Abstract. Involvement of the Na + / Ca 2+ exchanger in ouabain-induced inotropy and arrhythmogenesis was examined with a specific inhibitor, SEA0400. In right ventricular papillary muscle isolated from guinea-pig ventricle, 1 µM SEA0400, which specifically inhibits the Naexchanger by 80%, reduced the ouabain (1 µM)-induced positive inotropy by 40%, but had no effect on the inotropy induced by 100 µM isobutyl methylxantine. SEA0400 significantly inhibited the contracture induced by low Na + solution. In HEK293 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 24 publications
(8 reference statements)
2
30
0
Order By: Relevance
“…This was in contrast with the effects of KB-R7943, a compound that has been widely used as an NCX inhibitor; KB-R7943 inhibited all of the above mentioned currents with equal potency (8). Thus, SEA0400 was established as the first specific pharmacological tool to study the role of NCX and was shown to be useful in studies on myocardial excitation-contraction mechanisms, regulation by autonomic transmitters, and ischemia-reperfusion injury (5,10,11). In the present study, we examined the effects of SEA0400 and ryanodine on the spontaneous and ouabain-induced electrical activity of the guinea-pig pulmonary vein myocardium to clarify the role of NCX in automaticity.…”
Section: +mentioning
confidence: 99%
“…This was in contrast with the effects of KB-R7943, a compound that has been widely used as an NCX inhibitor; KB-R7943 inhibited all of the above mentioned currents with equal potency (8). Thus, SEA0400 was established as the first specific pharmacological tool to study the role of NCX and was shown to be useful in studies on myocardial excitation-contraction mechanisms, regulation by autonomic transmitters, and ischemia-reperfusion injury (5,10,11). In the present study, we examined the effects of SEA0400 and ryanodine on the spontaneous and ouabain-induced electrical activity of the guinea-pig pulmonary vein myocardium to clarify the role of NCX in automaticity.…”
Section: +mentioning
confidence: 99%
“…The microscope was IX-70 (Olympus, Tokyo) and the objective was UApocromat 40x / 340 water immersion (Olympus). The cells were excited at 360 nm from a Xenon lamp and the emission bands, 395 to 415 nm and 470 to 490 nm, were separated (W-VIEW system; Hamamatsu Photonics, Hamamatsu), detected by a high-speed cooled CCD camera (C6790, Hamamatsu Photonics), and ratioed after correction of background fluorescence (Aquacosmos software, Hamamatsu Photonics) as in our previous studies (11,12).…”
Section: +mentioning
confidence: 99%
“…Therefore, the most important requirement for a NCX inhibitorbeyond potent blocking of NCX -is a minimal influence on the I CaL current. In previous studies of our laboratory (10,28,55,83,84), we reported that ORM-10103 effectively (Figure 7.) and selectively inhibits NCX in dog ventricular myocytes without influencing the I CaL current (figure not shown). Furthermore it was effective against triggered arrhythmias, namely it clearly decreased the amplitude of pharmacologically induced EAD and reduced the DAD incidence.…”
Section: Orm-10103mentioning
confidence: 64%
“…The antiarrhythmic effect of selective NCX inhibition is controversial in the literature (43). NCX inhibitors have shown antiarrhythmic effects in hearth rhythm disturbances evoked by ischemia/reperfusion injury in vivo (44), in Langendorff perfused hearts (45)(46)(47)(48)(49)(50)(51), and in pharmacologically simulated ischemia/reperfusion models (52)(53)(54)(55)(56). The SEA0400 decreased the incidence (56), and reduced the development of EADs (57), it failed to suppress the aconitine induced arrhythmias (58).…”
Section: Transmural Heterogeneity In the Ventricular Myocardiummentioning
confidence: 99%
See 1 more Smart Citation